The Positive Relationships Between Paranoia, Perceptions of Workplace Bullying, and Intentions of Workplace Deviance in United Kingdom and French Teachers: Cross-Cultural Aspects - Lopes, Bárbara Cristina Da Silva; Bortolon, Catherine; Macioce, Válerie; Raffard, Stéphane (Frontiers in Psychiatry, 2020)
Cognitive models of psychopathology were applied to inform the relationships between paranoid cognitions, perceptions of workplace bullying, and intentions of workplace deviance in UK and French teachers. Sixty-six UK teachers and 50 French teachers were asked to fill in an online survey comprised of the Green Paranoia Thought Scales, Negative Acts Questionnaire, Depression, Anxiety and Stress scales, and Workplace Deviance Scale. The variables in this study were conceptualized as cognitions and not as facts because the study used self-report questionnaires of paranoid ideation, workplace bullying, and workplace deviance. Mann-Whitney tests showed that UK teachers report significantly more perceptions of work-related bullying and intentions of workplace deviance than French teachers. However, there was no statistically significant difference between UK and French teachers for the report of paranoid ideation. Mediation analyses showed that paranoia impacted on intentions of workplace deviance but perceptions of workplace bullying and negative affect did not mediate this association in UK and French teachers. Culturally tailored psycho-social interventions should be implemented targeting teachers' paranoid thinking and workplace bullying in order to deter teachers from engaging in workplace deviance and to promote their well-being.